Improved MDA compression for accelerated linear system solutions and monopolar basis functions for accurate MFIE formulations - Ubeda, E.; Heldring, A.; Rius, Juan M.; Espinosa, H.; Tamayo, J. M.; Parron, J. (2007 Computational Electromagnetic Workshop, 2007)
We present some of the recent advances in computational electromagnetics developed at AntennaLab, UPC. The paper focuses on two research lines: Firstly, an improved version of the multilevel matrix decomposition algorithm (MLMDA) is presented. This new approach lends itself to both traditional iterative and direct solutions of the linear system. Secondly, the monopolar basis functions, a new highly accurate set for the magnetic-field integral equation (MFIE) is presented.